Immunoregulatory and anti-HIV-1 enzyme activities of antioxidant components from lotus (Nelumbo nucifera Gaertn.) rhizome. Issue 5 (5th August 2011) - Jiang, Yun; Ng, Tzi Bun; Liu, Zhaokun; Wang, Changrong; Li, Ning; Qiao, Wentao; Liua, Fang
Abstract : In the present study, two antioxidant micromolecular components (L2f-2 and L2f-3) and an antioxidant macromolecular component LB2 were extracted from lotus ( Nelumbo nucifera Gaertn.) rhizomes. MS, FTIR (Fourier-transform IR) spectroscopy and NMR were used to identify these compounds. L2f-2 was (+/−)-gallocatechin, L2f-3 was (−)-catechin and LB2 was a polysaccharide–protein complex with a molecular mass of 18.8 kDa. LB2 was identified as a polysaccharide sulfate containing α/β-pyranose and α-furanose according to its FTIR spectrogram. It was composed of mannose, rhamnose, glucose, galactose and xylose with a molar ratio 2:8:7:8:1. The antioxidant components L2f-2, L2f-3 and LB2 strongly inhibited HIV-1 RT (reverse transcriptase) and IN (integrase). LB2 inhibited RT with an IC50 value of 33.7 μM. It also exhibited the highest HIV-1 3′-processing inhibitory activity with an IC50 value of 5.28 μM. Both L2f-2 and L2f-3 up-regulated the expression of IL-2 (interleukin-2) and down-regulated IL-10, while LB2 exhibited positive regulation on IL-2, IL-4 and IL-10. Moreover, L2f-3 and LB2 might inhibit HIV-1 directly by down-regulating TNFα (tumour necrosis factor α). These natural antioxidant components with antiviral and immunoregulatory activities could be potentially important for anti HIV-1 drug development and application to HIV-1 therapy.